ALTERNATIVE PLASTIC BOX 260 ASSEMBLY LINE USING HEURISTIC METHOD AND SIMULATION METHOD APPROACH TO INCREASE ASSEMBLY LINE EFFICIENCY - Yudha, Sabdha Purna; Pratikto, Pratikto; Tama, Ishardita Pambudi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2017)
assembly is the one step on productions. Efficiency of assembly line is affecting to the level of production. To increase the level of production, the efficiency of assembly line must increase to. Aims of this research is to create the alternative assembly line with using heuristic method and simulation approach, to meet higher level of efficiency and increase the assembly line capacity. The result from this research could increase the efficiency of assembly line from 53,2% to 91,5%, and result from simulation approach could increase capacity of assembly line from 9035 box per month to 11249 box per month